PENGARUH PRESTASI KERJA, PENDIDIKAN, PENGALAMAN KERJA, PENGENALAN, DAN KESEMPATAN UNTUK TUMBUH TERHADAP PENGEMBANGAN KARIR PEGAWAI NEGERI SIPIL PADA KANTOR DINAS KETENTRAMAN KETERTIBAN DAN SATUAN POLISI PAMONG PRAJA KOTA DENPASAR - SISKARINI JAYANTI, ANAK AGUNG SAGUNG; KETUT NETRA, GUSTI SALIT (E-Jurnal Manajemen; Vol 2 No 9 (2013), 2013)
The purpose of this research is to analyze the effect of job performance, education, experience, recognition, and opportunities to grow simultaneously or partially on the career development of civil servants, and to find out which are the most dominant variables affecting the development of the career civil servants. Data collected through interviews, observation, document study, and questionnaires. The study population was a civil servant at the Office of Peace Order and Civil Service Police Unit of Denpasar. Samples taken in stratified random sampling as many as 61 respondents. Results of this study indicate that work performance, education, work experience, recognition and the opportunity to grow simultaneously influence the career development of civil servants, while the variable only partially Education, recognition and the opportunity to grow that have an influence on the career development of civil servants in which variables are the most dominant influence on the career development of civil servants is the recognition variable. The implications of this study that the increasing need for any career civil servants to introduce themselves to the officials of the authority that decides in employee career development and actively engage the career development of civil servants at the Office of Peace Order and Civil Service Police Unit for the presentation of the activities carried out in inside and outside the organization, both as participants and speakers. Keywords: Career Development for Civil Servants